2019
DOI: 10.1007/s12528-019-09209-y
|View full text |Cite
|
Sign up to set email alerts
|

Blockchain-based approach to create a model of trust in open and ubiquitous higher education

Abstract: Currently, the training of the future work force presents challenging problems to higher education. This training, in the form of practical and theoretical knowledge can come from multiple platforms, channels and means, both formal and informal. In addition, it is quite difficult to assess the knowledge skill level that a student has acquired to optimize their chances for future employability. This, together with the need to still manage academic curricula on paper, the problems of confidence when validating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
97
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 208 publications
(102 citation statements)
references
References 2 publications
(1 reference statement)
0
97
0
5
Order By: Relevance
“…Due to the previously mentioned benefits, different authors have proposed the use of blockchain and other DLTs for developing applications for smart campuses and universities. Specifically, blockchain has been suggested for guaranteeing education certificate authenticity [57,58], managing digital copyright information [59], verifying learning outcomes [60,61], or enhancing e-learning interaction [62]. More potential smart campus applications and a deeper analysis on their characteristics can be found in [11][12][13]46].…”
Section: Blockchain For Smart Campuses and Universitiesmentioning
confidence: 99%
“…Due to the previously mentioned benefits, different authors have proposed the use of blockchain and other DLTs for developing applications for smart campuses and universities. Specifically, blockchain has been suggested for guaranteeing education certificate authenticity [57,58], managing digital copyright information [59], verifying learning outcomes [60,61], or enhancing e-learning interaction [62]. More potential smart campus applications and a deeper analysis on their characteristics can be found in [11][12][13]46].…”
Section: Blockchain For Smart Campuses and Universitiesmentioning
confidence: 99%
“…Studies have confirmed that trust is dependent on the agency of an IT to perform a definite task (Lizcano et al 2019;Teo et al 2005). Regarding the mobile payment scenario, the skill is considered as the capability credence, which enables the merchants to trust that the mobile payment is suitable in attaining the anticipated objective and hence execute the intended level of performance.…”
Section: Adoption Intention Of Mobile Payment Based On Merchant Trustmentioning
confidence: 99%
“…Grather et al 71 Smart contract for certification Turkanović et al 73 Transparent and technologically platform for higher education system Lizcano et al 72 Consensus mechanism for assessing the student Spearpoint et al 74 Payment system for peer-reviewing Bore et al 75 Maintain school records up to date Olnes et al 76 Authentication for documents in government organizations Dunphy et al 77 Decentralization platform for identity management 68 However, there is a necessity to enhance the transfer time for exchanging the security key for establishing the connection. Lei et al 69 proposed a model for speed transferring of security key between the vehicle's network.…”
Section: Author Functionmentioning
confidence: 99%
“…Grather et al, 71 in the education platform certification, play a vital role in deciding the achievement of an individual, and even after the completion of any training course, an individual receives a paper document. Lizcano et al 72 have misleading in publishing and sharing the documents by creating dilemmas over choosing the skill of teachers and students. Turkanovic et al 73 assit in availability of records and other materials in the distributed network make accessible for individuals and institutions for validating the history of the individual academic performance in a transparent manner.…”
Section: Educationmentioning
confidence: 99%